Innovative Technologies for Cultural Heritage. Tattoo Sensors and AI: The New Life of Cultural Assets - Talamo, Maurizio; Valentini, Federica; Dimitri, Andrea; Allegrini, Ivo (Sensors (Basel, Switzerland), 2020)
Conservation and restoration of cultural heritage is something more than a simple process of maintaining the existing. It is an integral part of the improvement of the cultural asset. The social context around the restoration shapes the specific actions. Today, preservation, restoration, enhancement of cultural heritage are increasingly a multidisciplinary science, meeting point of researchers coming from heterogeneous study areas. Data scientists and Information technology (IT) specialists are increasingly important. In this context, networks of a new generation of smart sensors integrated with data mining and artificial intelligence play a crucial role and aim to become the new skin of cultural assets.